Optimasi Setting Posisi Screen dan Blower terhadap Kapasitas serta Granulasi pada Proses Grinding di PT. Malindofeedmill, Tbk Grobogan - Dimas Ardiansyah Halim; Mukhlis Ibrahim; Muhammad Syahrul Sidiq; Kautzar Rizki Diptaseptian (Accurate: Journal of Mechanical Engineering and Science, 2020)
The efforts to increase capacity while maintaining the granulation of the grinding process are carried out to maximize the use of the hammer mill machine, which is the second largest electric energy consumption in a plant. The method that can be done to achieve this is by setting the screen position and setting the right blower opening. Standard screen specifications will maximize the capacity of the grinding process and produce optimum granulation. In order to get the maximum grinding capacity, DFCO can be set at the maximum but will have an effect on the motor current during the grinding process, the average current will tend to be high. The aim of this research was to determine the effect of variations in the screen’s and blower’s position settings on the capacity and granulation of raw materials from the grinding process. The usage of 2.5 mm and 3 mm diameters screens, as well as adjusting the screen position of 2.5 mm at the top and 3 mm at the bottom, resulted in better capacity and granulation than using a screen with only 3 mm diameter. The larger the blower and DFCO openings, the greater the grinding capacity, but also increased the motor current. The larger the blower opening, the greater the decrease in the water content of grinding raw materials.